Are learning styles relevant to virtual reality? - Chen, Chwen Jen; Seong, Chong Toh; Wan, Mohd Fauzy (ISTE (International Society for Technology in Education), 2005)
This study aims to investigate the effects of a virtual reality (VR)-based learning environment on learners with different learning styles. The findings of the aptitude-by-treatment interaction study have shown that learners benefit most from the VR (guided exploration) mode, irrespective of their learning styles. This shows that the VR-based environment offers promise in accommodating individual differences in terms of learning style. In addition, the significant positive effect of the VR (guided exploration) mode—which provides additional navigational aids—over the VR (non-guided exploration) mode—which does not provide additional navigational aids—also implies the importance of providing VR-based learning environments with proper instructional design to achieve the desired educational outcomes.